David Perry on game design : a brainstorming toolbox. - Perry, David, ....-; DeMaria, Rusel, ....- (Boston : Course Technology, 2009)
Part I: How to Use This Book Chapter 1: Using This Book as a Reference Chapter 2: Brainstorming and Research Part II: Which Game Will You Make? Chapter 3: Hooks Chapter 4: What Publishers Want Chapter 5: Game POV and Game Genres Chapter 6: Business Models Chapter 7: Branding Chapter 8: Protecting Your Intellectual Property Part III: Storytelling Chapter 9: Storytelling Techniques Chapter 10: Movie Genres Chapter 11: Scenarios Part IV: Characters Chapter 12: Character Design Chapter 13: Character Roles and Jobs Chapter 14: Enemies Chapter 15: Character Abilities Chapter 16: Speech Part V: Worlds Chapter 17: Game Worlds Chapter 18: Travel Chapter 19: Objects and Location Chapter 20: Music and Sound Part VI Experience Design Section A: The Elements of Experience Chapter 21: Experiential Design Chapter 22: Game Conventions and Cliches Section B: Goals and Rewards Chapter 23: Goals Chapter 24: Rewards, Bonuses, and Penalties Section C: Obstacles Chapter 25: Barriers, Obstacles, and Detectors Chapter 26: Traps and Counter Traps Chapter 27: Puzzles Section D: Time Chapter 28: Controlling Pacing Section E: Communication Chapter 30: Ways to Communicate with the Player Section F: Common Problems Chapter 31: Common Game Design Problems Chapter 32: Ways to Die Part VII: Weapons and Armor Chapter 33: Historical and Cultural Weapons Chapter 34: Standard Modern Weaponry and Armor Chapter 35: Epilogue
Keywords: Computerspelen